Question

Solve for Y 5(-y-9)-6y=1

255

likes1277 views

Lurline

4.6

81 Answers

First, distribute the 5 to both terms inside the parentheses:

5(-y - 9) = 5(-y) + 5(-9) = -5y - 45

The equation now becomes:

-5y - 45 - 6y = 1

Combine like terms on the left side:

-11y - 45 = 1

Add 45 to both sides to isolate the term with y:

-11y - 45 + 45 = 1 + 45

-11y = 46

y=\frac{46}{-11}

The equation now becomes:

Combine like terms on the left side:

Add 45 to both sides to isolate the term with y:

Frequently asked questions (FAQs)

How many different ways can 3 students be chosen from a class of 10 for a group project?

+

What is the limit as x approaches 3 of (2x + 1)/(x² - 9)?

+

Math question: Find the equation of a parabola with the vertex (2, -3) that opens upwards.

+

New questions in Mathematics